Pilkada Serentak and Constitutional Compliance: Fiscal Rationalization vs. the Quality of Local Political Representation in Decentralized Indonesia - Jabaruddin Jabaruddin (Yayasan Cipta Anak Bangsa (YCAB) Publisher, 2026)
Background: Indonesia’s simultaneous regional elections (Pilkada serentak) constitute a key component of post-Reformasi decentralization. While designed to strengthen democratic local governance, recent fiscal rationalization policies have increased central control over election financing, raising concerns about their impact on substantive democratic representation. Objectives: This study examines whether fiscal rationalization in Pilkada implementation supports or undermines constitutional principles of democratic, participatory, and accountable local government. It analyzes the constitutional framework of Pilkada, identifies key fiscal rationalization mechanisms, and evaluates their effects on local political representation. Methods: A qualitative normative empirical approach was employed. Normative analysis examined the 1945 Constitution, electoral and regional governance laws, fiscal decentralization regulations, and Constitutional Court decisions. Empirical analysis was conducted through comparative case studies of regional election budget management. Results: Four major mechanisms were identified: NPHD budget revisions, APBD burden-shifting, compressed electoral timelines, and intensified central fiscal steering under Law No. 1 of 2022. These mechanisms reduced electoral capacity, limited voter-candidate engagement, and disproportionately affected less-resourced regions. Although elections formally complied with constitutional requirements, substantive representation was weakened, creating a persistent gap between procedural legality and democratic quality. Conclusion: Fiscal rationalization has strengthened formal compliance but constrained substantive democratic representation. Greater fiscal stability and regional autonomy are needed to ensure competitive, equitable, and accountable local elections. Keywords: fiscal rationalization; Pilkada serentak; constitutional compliance; democratic representation; decentralization.